Treatment of ventricular tachycardia in patient with a mechanical aortic valve by radiofrequency catheter ablation via transseptal approach - Esenboga, Kerim; Sahin, Ebru; Vurgun, Kutay; Candemir, Basar; Altin, Timucin; Akyurek, Omer (Annals of Medical Research, 2021)
None